2011
DOI: 10.1186/1475-9276-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Health equity in the New Zealand health care system: a national survey

Abstract: IntroductionIn all countries people experience different social circumstances that result in avoidable differences in health. In New Zealand, Māori, Pacific peoples, and those with lower socioeconomic status experience higher levels of chronic illness, which is the leading cause of mortality, morbidity and inequitable health outcomes. Whilst the health system can enable a fairer distribution of good health, limited national data is available to measure health equity. Therefore, we sought to find out whether he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 10 publications
1
72
0
Order By: Relevance
“…Second, studies have also shown that public spending favors mostly the better-off rather than the poor (Castro-Leal et al, 2000;Wagstaff, 2002), and that the delivery of health care services remains extremely unequal (Almeida et al, 2000;Sheridan et al, 2011). A study by Mahal et al (2001) revealed that public financed curative health care services in India are more likely to serve richer segments of the population than the poor.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies have also shown that public spending favors mostly the better-off rather than the poor (Castro-Leal et al, 2000;Wagstaff, 2002), and that the delivery of health care services remains extremely unequal (Almeida et al, 2000;Sheridan et al, 2011). A study by Mahal et al (2001) revealed that public financed curative health care services in India are more likely to serve richer segments of the population than the poor.…”
Section: Discussionmentioning
confidence: 99%
“…Biculturalism has challenged New Zealand society to confront racial inequity and its debate has promoted societal recognition of human rights [57]. New Zealand has struggled to put equity principles into practice, indicating will without enactment.…”
Section: Resultsmentioning
confidence: 99%
“…New Zealand healthcare has a fractured system of individual authorities with little or no governmental policies to address healthcare inequity and develop synchronous policies across the many DHBs. Detailed planning and the implementation of healthcare policy was devolved to DHBs who often further devolved responsibility to PHOs [57]. Despite inequities being recognised in DHB strategic documentation they have not been addressed systematically below this level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address inequities, she argues, one needs to embed and sustain equity in organisational culture, practice, policies, and systems. Both Sheridan et al (2011) and Cram (2014a, b) have investigated how equity can be enhanced within the context of the health sector.…”
Section: Reducing Social Inequities: the Equity Imperativementioning
confidence: 99%